Inner speech deficits in people with aphasia - Langland-Hassan, Peter; Faries, Frank R.; Richardson, Michael J.; Dietz, Aimee (Frontiers in Psychology, 2015)
Despite the ubiquity of inner speech in our mental lives, methods for objectively assessing inner speech capacities remain underdeveloped. The most common means of assessing inner speech is to present participants with tasks requiring them to silently judge whether two words rhyme. We developed a version of this task to assess the inner speech of a population of patients with aphasia and corresponding language production deficits. Patients’ performance on the silent rhyming task was severely impaired relative to controls. Patients’ performance on this task did not, however, correlate with their performance on a variety of other standard tests of overt language and rhyming abilities. In particular, patients who were generally unimpaired in their abilities to overtly name objects during confrontation naming tasks, and who could reliably judge when two words spoken to them rhymed, were still severely impaired (relative to controls) at completing the silent rhyme task. A variety of explanations for these results are considered, as a means to critically reflecting on the relation between inner speech and silent rhyme judgments more generally.